2005
DOI: 10.1007/s00442-005-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing reproductive success in the clonal moss, Hylocomium splendens

Abstract: Female reproductive success in the unisexual perennial clonal moss Hylocomium splendens was examined by recording, if the segment was reproductive [produced sporophyte(s)] or not, together with several distance-to-male and male density variables, and segment size. This was done for every female segment in a population over a 5 year study period. A high fraction of the population could be sexed because we monitored the population in situ for 5 years, and thereafter harvested the population for electrophoretic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
(71 reference statements)
0
26
0
Order By: Relevance
“…Sexual reproduction and the production of sporophytes in mosses may be reduced by sperm-limitation [43,46], resource limitation [24,56,58,59], and abiotic stress ( [8]; Eppley et al [25]). Our experimental warming treatments increased sporophyte production in two moss species, P. alpinum and B. patens, compared with controls (Tables 2a and 3), and this warming potentially altered many steps in the process of sporophyte formation, from sperm and egg production, to gamete dispersal, to fertilization success, to sporophyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual reproduction and the production of sporophytes in mosses may be reduced by sperm-limitation [43,46], resource limitation [24,56,58,59], and abiotic stress ( [8]; Eppley et al [25]). Our experimental warming treatments increased sporophyte production in two moss species, P. alpinum and B. patens, compared with controls (Tables 2a and 3), and this warming potentially altered many steps in the process of sporophyte formation, from sperm and egg production, to gamete dispersal, to fertilization success, to sporophyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sexual reproduction requires specific demands for substrate quality (Laaka-Lindberg 2000), colony structure (e.g. Bowker et al 2000;Laaka-Lindberg 2003, 2004;Rydgren et al 2006) and climatic conditions (LaakaLindberg 2005). Consequently, the success of sexual reproduction, which forms a significant part of the life history, encompasses high temporal and spatial variability (Rydgren Table 6 The deposition percentage of the produced progules by the source and the cumulative numbers of propagules that were daily deposited from the source colony up to 10 m. As in Table 3, spore production is measured per day, but gemma production refers to the entire production in the standing gemma population 3.6 (1900) 2.4 (2600) 1.5 (6000) 0.009 (2600) 0.16 (294 · 10 3 ) 0.02 (73 · 10 3 ) 250 9.7 (5000) 6.5 (7000) 3.9 (16 · 10 3 ) 0.02 (5800) 0.6 (1.1 · 10 6 ) 0.08 (280 · 10 3 ) 500 20.4 (11 · 10 3 ) 13.8 (15 · 10 3 ) 8.3 (34 · 10 3 ) 0.04 (11 · 10 3 ) 1.7 (3.1 · 10 6 ) 0.23 (775 · 10 3 ) 1000 43.1 (23 · 10 3 ) 29.2 (31 · 10 3 ) 17.5 (72 · 10 3 ) 0.07 (19 · 10 3 ) 4.8 (8.7 · 10 6 ) 0.64 (2.1 · 10 6 ) and Økland 2002; Rydgren et al 2006).…”
Section: Production Of Spores and Gemmae And Deposition Within Coloniesmentioning
confidence: 99%
“…However, fertilization ranges are generally much shorter. Rydgren et al (2006) found, for example, that 85% of the female shoots with sporophytes were situated within a distance of 5 cm from the nearest male and the longest distance was 11.6 cm. Sexual reproduction in unisexual species may be further challenged by: the strongly biased sex ratio of their populations (Bisang et al, 2014); the spatial segregation of the sexes due to differences in niche preference between males and females (Stark & McLetchie, 2006;Brzyski et al, 2014; but see Bisang et al, 2015); and the potential incompatibility between certain male and female genotypes in unisexual species (McLetchie, 1996).…”
Section: Introductionmentioning
confidence: 99%